Theoretical aspects of some 4-[2,6-substituted-9H-purin-9-yl]-2-cyclopentene-1-methanol derivatives as anti-HIV agents - Türker, L; Sudagidan, M (Akademiai Kiado, 2000)
Some (-)-(1S,4R) -4-[2-amino-6-(substituted)-9H-purin-9-yl]-2-cyclopentene-1-methanol derivatives have been considered for semiempirical treatment at the level of AM1 type calculations. Certain theoretical structure-activity relationship were investigated.
Keywords: Carbocyclic Nucleoside Analog; Aids-Related Complex; Potent; Infection; 1592u89